(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: This study aimed to describe the clinical, paraclinical characteristics, pathogens, antimicrobial susceptibility of spontaneous bacterial peritonitis in cirrhotic patients. Methods: A descriptive case-series study was conducted on spontaneous bacterial peritonitis patients with cirrhosis upper 16 years old who were treated at the hospital for Tropical Diseases between January 2022 to August 2024. Results: Fever ≥ 38oC was in 64.6% of patients, followed by abdominal pain (74.6%); 10.5% of patients presented with neither fever nor abdominal pain; 71,8% of patients had white blood cells <12 000/mm3. Ascitic fluid cultures were positive in 58.9% of cases, of which over 90% of the isolates were Gram-negative bacteria. Escherichia coli were found to be the predominant agent isolated from the ascitic fluid infections (55%) followed by Klebsiella pneumoniae (25%) and Streptococcus sp. (7,5%). The susceptibility rate of E.coli to ceftriaxone and piperacillin/tazobactam was 65% and 88%, respectively. Carbapenem-resistant E.coli accounted for 9.9% of isolates. The susceptibility rate of K.pneumoniae to ceftriaxone and piperacillin/tazobactam was 83.9% and 93.3%, respectively. The mortality rate was 26%. Conclusion: In decompensated cirrhosis, spontaneous bacterial peritonitis must be considered through thorough clinical evaluation, even if the patient is afebrile and lacks abdominal pain or an elevated white blood cell count. The susceptibility of E.coli to ceftriaxone has increased compared to previous study. However, carbapenem resistance was observed.